PENGELOLAAN BANTUAN SISWA MISKIN DI SMP MUHAMMADIYAH 8 WONOGIRI - Heru Mahmudi Santoso; Yetty Sarjono; Wafrotur rohmah (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aims of the research are to: 1) describe the preparation of management of Student Financial Aid Program; 2) describe the activities of management of Student Financial Aid Program; and 3) describe the management report of Student Financial Aid Program at SMP Muhammadiyah 8 Wonogiri. The research method applied was descriptive qualitative study by using an ethnographic approach. The subject of the research was SMP Muhammadiyah 8 Wonogiri. The data were collected through in-deep interview, observation and documentation. The informants of the research are: the principal, vice-principal, and teachers, who have the role in Poverty Student Aids management of SMP Muhammadiyah 8 Wonogiri. The data were obtained and analyzed by using an interactive model which included data collection, reduction, verification and drawing conclusion. The research result showed that; 1) The preparation of management of Student Financial Aid Program at SMP Muhammadiyah 8 Wonogiri was started by conducting a coordination among the principal, teachers, staffs, and team. Then they prepared some data related to students’ background which would be promoted to get Student Financial Aid Program ; 2) The activities in managing of The Student Financial Aid Program was started by planning, actuating, distributing, recording, controlling, and reporting of Student Financial Aid Program as a form of responsibility of the team in managing Student Financial Aid Program, and 3) In the end of management process of Student Financial Aid Program, school or the team had a responsibility to record and report the outcome of the management of Student Financial Aid Program at SMP Muhammadiyah 8 Wonogiri. By reporting the outcome, it meant that the management of Student Financial Aid Program had been finished. The whole management activities of Student Financial Aid Program were based on the principles of School Financial Management, those are; transparency, accountability, effectively, efficiency. And effective